Aramaic Daniel Apocryphon (4Q246) - Krajnc, Aljaž (Bogoslovni vestnik, 2025)
The Aramaic Daniel Apocryphon (4Q246) is among the most discussed Aramaic texts from Qumran, primarily due to its mention of a figure called the “Son of God” (??? ?? ??) and the “Son of the Most High” (?? ?????). The fragmentary state of the scroll and its syntactic ambiguity have generated divergent interpretations, with some seeing the figure as a blasphemous foreign king and others as a positive, eschatological savior. This study reexamines 4Q246 through a fresh philological and structural analysis. It contains the edition, transla -tion, and detailed linguistic commentary of the text, together with a new proposal for dividing the work according to the alternation of positive and negative parts (A1–B1, A2–B2, A3–B3), which clarifies the internal structure of the text. Although the text changes the period it describes three times, the logical referents of the descriptions are only two periods, negative and positive. The analysis supports understanding the “Son of God” not as a negative or arrogant ruler, but as a positive, messianic figure who combines Davidic royal ideology with Danielic apocalyptic themes. Finally, the paper points out similarities between 4Q246 and Luke 1:32-35, suggesting they share theological ideas rather than having a direct literary connection.
Keywords: 4Q246; apocalyptic literature; apokaliptična literatura; Aramaic Daniel Apocryphon; aramejski Danielov apokrif; Božji Sin; Davidic messianism; Dead Sea Scrolls; kumranska aramejščina; Luka 1,32-35; Luke 1:32-35; mesija iz Davidovega rodu; Mrtvomorski rokopisi; Qumran Aramaic; Son of God; Son of Man